Crystal engineering, electron density analysis, and in situ variable temperature studies on co-crystal between nicotinic acid and gallic acid sesquihydrate. Issue 5 (5th January 2023) - Iqbal, Infal; Mehmood, Arshad; Noureen, Sajida; Lecomte, Claude; Ahmed, Maqsood
Abstract : The growth and thermal stability of the gallic acid : nicotinic acid cocrystal has been analyzed in terms of electron density analysis and conversion of GA monohydrate into anhydrate through heating the co-crystal. Abstract : A combined thermal analysis, variable temperature diffraction analysis, and X-ray charge density analysis of 2 : 2 nicotinic acid : gallic acid (NAGA). 3H2 O co-crystal is reported, which revealed the dynamics of co-crystal growth. The precursor gallic acid monohydrate transforms to gallic acid anhydrate upon heating the co-crystal and as a result, the co-crystal assembly crumbles. To further explore the mechanism of the co-crystal growth, electrostatic and topological analysis of various intermolecular interactions in the co-crystal assembly, an experimental charge density analysis was performed using high-resolution diffraction data collected at 100 K and refined on the basis of Hansen and Coppens multipolar formalism using Mopro software. The results from the experimental refinements were compared with the multipolar refinement using theoretical structure factors obtained from B3LYP-D3 DFT calculations with excellent agreement. The co-crystallization starts with the formation of an NA⋯NA zwitterion backbone to which the hydrated gallic acid coformer binds via the electrostatic interactions. The significance of thermal analysis and in situ diffraction analysis combined with multipolar refinement has been proven to be helpful in understanding co-crystal growth. During in situ thermal diffraction analysis, the hydrated polymorph was transformed into another anhydrate polymorph of GA.